Evaluating outcome of prophylaxis in haemophilia: objective and self‐reported instruments should be combined. (8th February 2016) - Fischer, K.; Nijdam, A.; Holmström, M.; Petrini, P.; Ljung, R.; van der Schouw, Y. T.; Berntorp, E.
Abstract : Introduction: Routine outcome assessment of prophylaxis should use validated tools, while balancing comprehensiveness and burden. Collecting overlapping information should be avoided. Aim: To assess correlations between different outcome assessment tools in haemophilia. Methods: From an international cross‐sectional study, data on objective outcome (Haemophilia Joint Health Score (HJHS 2.1, range 0–124), radiological Pettersson score) and self‐reported joint bleeding, Haemophilia Activities List (HAL, range 100–0), health‐related quality of life (SF‐36, including five physical and five mental domain scores, range 100–0), and Utility (SF6D and EQ‐5D, range 1.0–0) were extracted. Spearman's correlations were calculated: ≥0.8 very strong, 0.60–0.79 strong, 0.40–0.59 moderate. Results: Ninety patients with severe haemophilia, on prophylaxis since median age 3.4 years, were evaluated at median 25.5 years (range 16.0–37.6). Objective outcome was favourable (median HJHS 2.1 6 points, Pettersson score 9 points). Self‐reported outcome showed a median of 7 joint bleeds in 5 years, median HAL sum 96 points, high scores for physical domains of SF‐36 (median 80–95) and high Utility values (median SF6D 0.87; EQ‐5D 0.84). Physical examination (HJHS 2.1) showed strong correlation with radiological scores, moderate correlation with physical domains of the SF‐36 and Utility, but no correlation with self‐reported bleeding or limitations in activities (HAL). Bleeding was not associated with any other outcome parameter. The HAL was only correlated with the SF36 'Physical functioning' domain. Conclusion: For the evaluation of patients on early prophylaxis, information on bleeding should be complemented by objective joint assessment as well as self‐reported limitations in activities and quality of life.